2014
DOI: 10.1155/2014/623651
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Antioxidant and Antimicrobial Activities of Extracts Obtained fromCrataegus azarolusL. var.aronia(Willd.) Batt. Ovaries Calli

Abstract: Objective. Plant cell culture is an innovative technology to produce a variety of substances. Numerous plants synthesize among their secondary metabolites phenolic compounds which possess antioxidant and antimicrobial effects. Hawthorn (Crataegus) is one of these plants which has long been used in folk medicine and is widely utilized in pharmaceutical preparations mainly in neuro- and cardiosedative actions. Methods and Results. The production of polyphenol by fifty-two-week-old Crataegus azarolus var. aronia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 58 publications
(92 reference statements)
6
24
2
2
Order By: Relevance
“…In some studies, the hawthorn extracts showed higher antibacterial activity than did in our study (Kostic et al,2012;Bahri-sahloul et al, 2014 ). There are differences between the results of mentioned studies.…”
Section: Resultscontrasting
confidence: 70%
“…In some studies, the hawthorn extracts showed higher antibacterial activity than did in our study (Kostic et al,2012;Bahri-sahloul et al, 2014 ). There are differences between the results of mentioned studies.…”
Section: Resultscontrasting
confidence: 70%
“…Phenolics may have a direct contribution in the antioxidant activity [10]. The antioxidant potential in various medicinal plants has been shown mainly due to phenolic compounds [11][12][13][14][15][16]. Likewise, different species of the genus Artemisia including A. absinthium L. have shown phenolics associated antioxidant activities [4,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies in which BAP and IBA plant growth regulators were used in equal amounts, shoot formations have been reported as results similar to our study 23,24 . When the literature is examined, many studies on the antimicrobial potential of medicinal plants produced by plant tissue culture attract the attention 25,26 . In this study, the antimicrobial potential of the Taraxacum officinale shoots obtained through propagation have been examined.…”
Section: Resultsmentioning
confidence: 99%